M05B5.4 (lysosomal phospholipase A2) promotes disintegration of autophagic vesicles to maintain C. elegans development. Issue 3 (4th March 2022) - Li, Yuan; Wang, Xin; Li, Meijiao; Yang, Chonglin; Wang, Xiaochen
ABSTRACT: The autophagosome has two lipid bilayer membranes. The outer membrane fuses with the lysosome, while the inner membrane is degraded to release autophagic contents for degradation. It remains unclear how the inner vesicle of the autophagosome (called the autophagic vesicle) is disintegrated after autophagosome-lysosome fusion. Here, we identified C. elegans LPLA-2/M05B5.4 as a key enzyme that degrades membranous material in lysosomes. LPLA-2 is homologous to human PLA2G15, a lysosomal phospholipase A2 family protein that catalyzes cleavage of membrane phospholipids. We found that loss of LPLA-2 causes accumulation of large membrane whor ls in enlarged lysosomes and both phenotypes are suppressed by blocking macroautophagy/autophagy. Moreover, autophagic vesicles persisted in enlarged lysosomes in PLA2G15 knockdown cells and lpla-2(lf) mutants, which suggests that the breakdown of the inner autophagosomal membrane in lysosomes is impaired. lpla-2(lf) mutants exhibit severe defects in both embryonic and larval development. Our data suggest that disintegration of the inner autophagosomal membrane by LPLA-2 promotes the release and subsequent degradation of autophagic contents in lysosomes, which is essential for C. elegans development. Abbreviations : ATG: autophagy related; EPG: ectopic PGL granules; GFP: green fluorescent protein; LGG-1: LC3, GABARAP and GATE-16 family; LPLA-2: lysosomal phospholipase A2; PGL: P granule abnormality protein; PLA2: phospholipase A2; SD: standard deviation; SEPA-1: suppressor of ectopic P granules in autophagy mutant; SQST-1: sequestosome related.